Produção de leite de cabra e fermentação ruminal, utilizando rações com levedura seca (Saccharmyces cerevisiae) - Lima, Luciano Soares de (2010)
This work was carried out to evaluate performance, milk quality, intake and digestibility in Saanen goats fed diets with dry yeast in replacement of soybean meal, and to evaluate the intake, digestibility and the ruminal fermentation parameters of diets with dry yeast in replacement of soybean meal in Saanen goats. In the performance trial 18 Saanen goats (± 51.07 kg) in milk were used allotted to a completely randomized design with factorial arrangement (3x2 - three diets and two ages at first kidding). Treatments were soybean meal (SB), soybean meal + dry yeast (SBDY) or dry yeast (DY) as a protein source. The other ingredients were ground corn, mineral mixture and corn silage (40%). Goats fed DY diet showed lower intake of dry matter (DM), organic matter (OM), crude protein, ether extract and neutral detergent fiber. Animals with two years at the first kidding had higher intake of DM and nutrients. Diets did not influence milk yield corrected for 3.5% of fat, but goats with one year at the first kidding showed lower milk yield than ones with two years. Acidity, density, somatic cell counts, milk and blood urea nitrogen did not change among treatments. Animals fed SBDY diet had higher fat and total solids than those fed DY diet. The digestibility of DM, OM and total carbohydrate were higher for DY diet than others. Total digestible nutrients were higher for DY and SB diets than SBDY diet. For evaluation of rumen fermentation parameters five castrated Saanen goats (± 48.19 kg) allotted to a 5 x 5 Latin square design were used. Treatments were levels of dry yeast replacing soybean meal (0, 25, 50, 75 and 100%). Diets were composed of corn silage (40%), ground corn, soybean meal and/or dry yeast and mineral mixture. The experimental periods were of 15 days (10 day for adaptation and five days for collection). The intakes of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), total carbohydrates (TC) and total digestible nutrients (TDN) were not influenced by the treatments. However, ether extract (EE) intake showed linear effect. There were no differences among treatments for the digestibility of DM, OM, CP, NDF and CT. However EE digestibility showed a quadratic effect. The TDN content did not change with the inclusion of dry yeast in the diets. The pH and N-NH3 concentration did not differ among diets. The short chain fatty acids content was not affected by treatments. However, acetate/propionate ratio showed a quadratic behavior. Ruminal digesta scanning electron microscopy observations did not indicate, apparently, microbial colonization and degradation changes. Dry yeast can be fed to dairy goats; it maintains the nutritional value, as well as milk yield and quality. Dry yeast can replace soybean meal in diets of Saanen goats without changing the ruminal fermentation pattern, intake and digestibility.